Factors affecting entrepreneurial intention among students in GIATMARA Wilayah Persekutuan - Mohd Apandi, Aini (2014)
Entrepreneurship in general is highly regarded as a catalyst for economic development. In fact, research on entrepreneurial intention has grown over the last decade. The purpose of this study was to identify whether the attitude toward the behaviour, subjective norm, perceived behavioural control and entrepreneurship education has a significant relationship with entrepreneurial intention among students in GIATMARA, Wilayah Persekutuan. The students pursue various courses to enhance the skills in fabric, culinary and multiple technical areas. Consequently, the questionnaire was developed and distributed to 214 students of GIATMARA in 12 branches in Wilayah Persekutuan. A total of 200 form returned and only 191 usable. The testing of the hypotheses involving the independent variables of attitude toward behaviour, subjective norm, perceived behavioural control and entrepreneurship education with the dependent variable of entrepreneurial intention was implemented using the method of Pearson’s Correlation Analysis and Multiple Regression Analysis. The Pearson’s Correlation results show that there are positive relationships between the independent variables with entrepreneurial intention. Meanwhile, Multiple Regression analysis proved that all independent variables except perceived behavioural control have a significant influence on entrepreneurial intention.